Unveiling the Power of Social Media and FOMO: How Hedonic Motivation Drives Impulsive Purchases of Cosmetic Products - Wisnu Mahendri; Ananda Zahwa Maulidiyah (Universitas Kadiri, 2025)
This study examines the influence of Social Media Marketing (SMM) and Fear of Missing Out (FOMO) on impulsive purchasing behavior among Generation Z consumers, with hedonistic shopping motivation as an intervening variable. The rapid growth of the cosmetics industry in Indonesia, driven by social media, makes this topic highly relevant for analysis. A quantitative method with a Structural Equation Modeling (SEM) approach using SmartPLS was applied to test the proposed hypotheses. The sample in this study consisted of 100 people obtained through purposive sampling. The results showed that SMM had a significant effect on hedonistic shopping motivation, while FOMO also had a significant effect on this motivation. Hedonistic shopping motivation was found to influence impulsive buying, but the direct effect of SMM on impulsive buying was not significant. FOMO was found to directly influence impulsive buying. Additionally, hedonistic shopping motivation acted as a full mediator in the relationship between SMM and impulsive buying, and as a partial mediator in the relationship between FOMO and impulsive buying. These findings emphasize the importance of emotional involvement and psychological factors in influencing impulsive buying behavior. The practical implication of this study is that marketers need to design content that can evoke emotional responses and create a sense of exclusivity, which can encourage consumers to make impulsive purchases, especially for cosmetic products.